Regulation of feeding behavior and psychomotor activity by corticotropin-releasing hormone (CRH) in fish - Matsuda, Kouhei (Frontiers in Neuroscience, 2013)
Corticotropin-releasing hormone (CRH) is a hypothalamic neuropeptide belonging to a family of neuropeptides that includes urocortins, urotensin I and sauvagine in vertebrates. CRH and urocortin act as anorexigenic factors for satiety regulation in fish. In a goldfish model, intracerebroventricular (ICV) administration of CRH has been shown to affect not only food intake, but also locomotor and psychomotor activities. In particular, CRH elicits anxiety-like behavior as an anxiogenic neuropeptide in goldfish, as is the case in rodents. This paper reviews current knowledge of CRH and its related peptides derived from studies of teleost fish, as representative non-mammals, focusing particularly on the role of the CRH system, and examines its significance from a comparative viewpoint.